THE INFLUENTIAL CONTRIBUTIONS OF AL-JUZŪLĪ TO ISLAMIC THEOLOGY THROUGH HIS PROLEGOMENA; ʿAQĪDAH AL-JUZŪLĪ AND THE AL-JUZŪLĪYYAH ṢUFĪ ORDER - Nurul Ain Kamarudin,; Ahmad Arif Zulkefli,; Mohammad Fahmi Abdul Hamid,; Khairul Azhar Meerangani, (Journal of Islamic, Social, Economics and Development, 2023)
In the 9th century of Hijrah, Muḥammad bin Sulaymān al-Juzūlī al-Soūsī was a prominent scholar of Ahl al-Sunnah wa al-Jama'ah al-Ashāʿirah. He continued the al-Shādhiliyyah sufī order established by Abū al-Ḥasan al-Shādhilī (d. 656H) and was a scholar who made many contributions to Islam, particularly in the field of sufīsm with his magnum opus, the book Dalāʾil al-Khayrāt, which became widely known, and other writings. To this day, Islamic scholars recognise him as a prominent sufī and aqidah figure, and his prominence is reflected in his sufī order, al-Juzūlīyyah, which is followed by many scholars, particularly in Morocco. Nonetheless, the contemporary researchers believe that the discussion regarding his contribution to the Islamic world, particularly through his prolegomena; ʿAqīdah al-Juzūlī, is lack of focus. The primary objective of this study is to identify his contribution in terms of the book's impact on Ahl al-Sunnah wa al-Jama'ah al-Ashāʿirah and its contribution to the Islamic world. This investigation employs a qualitative methodology. The method of data acquisition in this study is a literature review, and the primary source is the book ʿAqīdah al-Juzūlī. To obtain the accurate description of al-Juzūlī's role and contribution to the Islamic world, the data analysis method employs the content analysis methodology by referencing the turāth written by Muslim scholars. The study founds that Muḥammad bin Sulaymān al-Juzūlī was a renowned religious scholar who has significantly contributed to the proliferation of the al-Ashʿrī sect in the western Islamic world. The notion of faith that he emphasised can serve as a lesson and point of reference for Muslims, particularly in uniting Muslims who have recently been perceived as becoming more divided.